Injuries associated with bunk beds that occur in jail. (January 2018) - Loder, Randall T.; Young, Jocelyn Cole
Abstract: Background: There are many studies of bunk bed injuries, but none specifically addressing those occurring in jails. It was the purpose of this study to investigate the magnitude and patterns of bunk bed injuries occurring in correctional institutions. Methods: The National Electronic Injury Surveillance System (NEISS) data for the 10 year period 2006 through 2015 due to bunk beds was accessed. Injuries involving bunk beds were identified and the mechanism of injury determined. Statistical analyses were performed with SUDAAN 10™ software. A p < 0.05 was considered statistically significant. Results: There were an estimated 639, 505 ED visits for bunk bed associated injuries; 51, 204 occurred in jail. All jail cases occurred in the age groups ≥10 years (177, 165); 29% of these 177, 165 sustained the injury in jail. Those who sustained a bunk bed injury in jail compared to those who did not were older, more commonly male, seen in smaller hospitals, more likely admitted, and more frequently associated with a seizure. For those injuries occurring in jail, the most common injury in the trunk and lower extremity was a strain/sprain; the upper extremity a contusion/abrasion; and the head/neck a laceration or traumatic brain injury. A fall off the bunk bed accounted for 71.8% of the injuries, had the highest hospital admission rate (7.4%), accounted for all of the spine injuries, 96% of the head injuries, and had the highest proportion of fractures (14.4%). Inmates having a seizure before the injury sustained fewer fractures, more lacerations, and more head/neck injuries. Conclusions: Injuries in jail account for 29% of all bunk bed injuries resulting in an ED visit in the USA in those age groups ≥10 years. A fall from the bed occurred in 72% and a seizure disorder was 4.5 times more common in jail inmates compared to non inmates. Possible prevention strategies include railings/ladders to reduce the incidence of falls, changes in flooring surfaces, and seizure education and placing inmates with seizure and/or alcohol related disorders on the bottom bunk. This will require a multidisciplinary approach involving the disciplines of medicine, material engineering, and criminal justice. Highlights: Injuries associated with bunk beds occurring in jail account for 28.9% of bunk bed injury ED visits in those > 9 years old. A fall off the bunk bed accounted for 71.8% of the injuries. Seizure disorder is 4.5 times more common in jail inmates compared to others in those over 9 years of age.